2003
DOI: 10.1016/s1474-4422(03)00305-3
|View full text |Cite
|
Sign up to set email alerts
|

Vascular cognitive impairment

Abstract: Cerebrovascular disease is the second most common cause of acquired cognitive impairment and dementia and contributes to cognitive decline in the neurodegenerative dementias. The current narrow definitions of vascular dementia should be broadened to recognise the important part cerebrovascular disease plays in several cognitive disorders, including the hereditary vascular dementias, multi-infarct dementia, post-stroke dementia, subcortical ischaemic vascular disease and dementia, mild cognitive impairment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
731
0
41

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,146 publications
(800 citation statements)
references
References 79 publications
21
731
0
41
Order By: Relevance
“…Our results support the clinically based hypothesis that penetrating arterioles and arteries may be of central importance in small strokes (13,14). For example, subcortical regions are particularity vulnerable to ischemia that results in lacunar lesions, because the blood flow in these regions comes from relatively long penetrating arteries (27). The extent of ischemia we measured in rat around an occluded penetrating arteriole (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Our results support the clinically based hypothesis that penetrating arterioles and arteries may be of central importance in small strokes (13,14). For example, subcortical regions are particularity vulnerable to ischemia that results in lacunar lesions, because the blood flow in these regions comes from relatively long penetrating arteries (27). The extent of ischemia we measured in rat around an occluded penetrating arteriole (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Estimation of structural damage has been complemented by assessment of cerebral function using quantifiable, reproducible and sensitive neuropsychological indices of executive dysfunction, the hallmark of hypertensive subcortical cerebral disease. 11 Consistent with previous studies, van Boxtel et al 10 demonstrated higher systolic BP and pulse pressures to be related to the presence and severity of white matter lesion load. However, no clear relationship was demonstrated between white matter lesion load and cognitive performance parameters or between diurnal BP rhythm and structural or functional cerebral damage.…”
supporting
confidence: 84%
“…11,13 Second only to age, hypertension has been shown to the most important risk factor for small vessel disease [3][4][5][6] and a complex and dynamic relationship between BP and cerebral function is being revealed; high BP may initially accelerate arteriosclerotic change and impair cerebral autoregulation with adverse effects on cognition but high BP may be required for adequate perfusion when arteries are diseased and cerebral autoregulation is impaired. Uncertainty surrounds the appropriate level of BP for optimum cognitive performance and the desirability of lowering of BP beyond a certain level in patients with established cerebral small vessel disease continues to be a subject of much debate.…”
mentioning
confidence: 99%
“…Stroke is the second most common cause of acquired cognitive impairment, which predisposes patients toward institutionalization, disability, increased mortality, and poorer quality of life 1, 2, 3. With an aging population and a decline in mortality after stroke,4 the rates of poststroke cognitive impairment will increase.…”
Section: Introductionmentioning
confidence: 99%